ALTERNATIF RANCANG SISTEM PENGAMBILAN KEPUTUSAN UNTUK MENDUKUNG PENYELESAIAN ISU-ISU PERKEBUNAN KELAPA SAWIT - Lumbanraja, Pretty Luci; Naomi Elena Lumbanraja (LogicLink, 2024)
Decision support systems are a concept found in computer science where this concept can make it easier for decision makers to solve problems. It is hoped that this decision support system can help in making decisions on issues and problems that occur in oil palm plantations. The analysis technique for this research is qualitative descriptive using bibliometric results and literature reviews. The scope of the data used is published articles based on searches on the Scopus website. The published articles come from accredited international journals. The tools used in this research are Publish or Perish Version 8, Mendeley and VosViewer. From the results of this research, it was found that the decision-making system can support the resolution of issues, namely, increasing farmers' income, village economic development, regional economic growth (GRDP, income from palm oil importing countries, productivity of the palm oil industry, rural development, employment absorption, reduction poverty, use of fertilizers and pesticides, emissions and pollutants from industrial activities, governance and water needs.